Implementation of Multi Objective Optimization on the Basic of Ratio Analysis Method in Decision Support System for Hope Family Program Assistance Recipients in Kelinjau Ulu Village - Arsita; Salmon; Heny Pratiwi (Politeknik Pertanian Negeri Samarinda, 2021)
The research was conducted to be able to create a decision support system for beneficiaries of the Family Hope Program or “Program Keluarga Harapan (PKH)” with the Multi Objective Optimization Method On The Basic Of Ratio Analysis (Moora), which later if this research is successful it can assist aid managers in making decision making for program aid recipients Family Hope “PKH”. This research was conducted at the office of the Family Hope Program “PKH” assistance manager in Kelinjau Ulu Village, Muara Analog District, the data collection method used was interviews which asked questions related to “PKH” beneficiaries. By means of observation, namely making direct observations at the “PKH” Assistance Manager office. In this study, the system development method used is the decision support system development method. The model with the decision support software used is the Visual Basic.NET programming language, the database used by Microsoft Access. The final result of this research is in the form of a Decision Support System for beneficiaries of the Family Hope Program “PKH” Using the Multi Objective Optimization Method on the Basic of Ratio Analysis (Moora) which can facilitate more precise selection of “PKH” aid recipients.